The Effect Dimension of Servicescape on Revisit Intention : Study Case: Lotus Lounge Wyndham Opi Hotel Palembang - Anggraini, Meisya; Yuniarti, Rizka; Sari, Tasya Komara; Hamonangan, Samuel; Lesmana, Andhika Chandra (Journal of Mandalika Review, 2025)
Introduction: This research aims to determine the effect of servicescape on revisit intention at Lotus Lounge Wyndham Opi Hotel Palembang. Lotus Lounge locate at Wyndham hotel which is one of the 4-star hotels in Palembang City. This means that Lotus Lounge should be one of the cafés or lounges of choice for customers or visitors, because it is in a 4-star hotel, strategically located in the center of the crowd, and close to public transportation. Methodology: A quantitative descriptive approach was used in this study, with data analyzed using IBM SPSS Statistics version 25 to identify the most influential servicescape indicators on revisit intention. A total of 60 respondents were selected based on the Lemeshow sampling formula. Findings: The findings show that ambient condition emerged as the most influential indicator, with a mean score of 3.20. In contrast, the indicator Signs, Symbols, and Artifacts was identified as an area needing improvement particularly in the visibility of restroom signs, exit doors, and clear indicators for smoking and non-smoking zones. Conclusion: The ambient condition significantly affects guest comfort and revisit intention. Natural lighting from windows, the lounge’s strategic location near the lobby, and soothing background music, jazz and pop contribute to a relaxing and welcoming atmosphere. Additionally, proper temperature, pleasant aromas, and clear area signage enhance the overall guest experience. These combined elements position Lotus Lounge as a comfortable and inviting space for relaxation, socializing, and professional interactions encouraging guests to return in the future.